2004
DOI: 10.1002/gcc.20007
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous deletions within the 11q13 cervical cancer tumor‐suppressor locus in radiation‐induced, neoplastically transformed human hybrid cells

Abstract: Studies on nontumorigenic and tumorigenic human cell hybrids derived from the fusion of HeLa (a cervical cancer cell line) with GM00077 (a normal skin fibroblast cell line) have demonstrated "functional" tumor-suppressor activity on chromosome 11. It has been shown that several of the neoplastically transformed radiation-induced hybrid cells called GIMs (gamma ray induced mutants), isolated from the nontumorigenic CGL1 cells, have lost one copy of the fibroblast chromosome 11. We hypothesized, therefore, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Thus, the HeLa cells showed homozygous loss of the 5.5kb sequences. HeLa cell derived tumorigenic hybrid cell lines and a primary cervical tumor also showed homozygous loss of these sequences (represented by the STS marker D11S913) [3]. Surprisingly, we also found heterozygous loss of the same sequences in two fibroblast cell lines (GM00077 and GM00468).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, the HeLa cells showed homozygous loss of the 5.5kb sequences. HeLa cell derived tumorigenic hybrid cell lines and a primary cervical tumor also showed homozygous loss of these sequences (represented by the STS marker D11S913) [3]. Surprisingly, we also found heterozygous loss of the same sequences in two fibroblast cell lines (GM00077 and GM00468).…”
Section: Introductionmentioning
confidence: 56%
“…We have previously localized the HeLa cell homozygous deletion to a ~5.5kb interval of chromosome 11q13.1 [3] (Figure 1). While one of the deletions was 5.5kb, the other deletion was 2.3Mb.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that a cervical cancer tumor suppressor gene is localized to chromosome 11q13 and that genomic rearrangements at this site are common in cervical and other human cancers (13,14). We have further shown that homozygous deletion of 5.5kb is seen in HeLa cell derived tumorigenic cell lines and primary tumors indicating the importance of these sequences in tumor development (15)(16)(17). Extensive mapping of the 300kb region localized the 5.5 kb sequence to the 1 st intron of PACS-1, a protein involved in cytoplasmic protein trafficking (15)(16)(17).…”
Section: Introductionmentioning
confidence: 61%
“…We have further shown that homozygous deletion of 5.5kb is seen in HeLa cell derived tumorigenic cell lines and primary tumors indicating the importance of these sequences in tumor development (15)(16)(17). Extensive mapping of the 300kb region localized the 5.5 kb sequence to the 1 st intron of PACS-1, a protein involved in cytoplasmic protein trafficking (15)(16)(17). The repetitive nature of the 5.5 kb sequence made it extremely difficult to functionally characterize the sequence for its role in tumor development.…”
Section: Introductionmentioning
confidence: 72%
“…We and others have confirmed the involvement of chromosome 11 in cervical cancer by suppression of the tumorigenic phenotype with the transfer of chromosome 11 into cervical cancer cell lines (Saxon et al, 1986; Koi et al, 1989). Detailed cytogenetic and molecular genetic analysis of cervical cancer cell lines, non tumorigenic and tumorigenic HeLa cell hybrids, and primary tumors localized the gene to a 300 kb interval of 11q13 (Jesudasan et al, 1995; Srivatsan et al, 2002; Mendonca et al, 2004). CGH (comparative genomic hybridization) and SKY (spectral karyotyping) studies have identified translocations and amplifications at chromosome 11q13 in cervical cancer lines (Harris et al, 2003; Rao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%